2020
DOI: 10.1021/acsptsci.0c00004
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Signaling That Challenges Dogmata of G Protein-Coupled Receptor Regulated Functions

Abstract: Activation as well as recruitment of neutrophils, the most abundant leukocyte in human blood, to sites of infection/inflammation largely rely on surface-exposed chemoattractant receptors. These receptors belong to the family of 7-transmembrane domain receptors also known as G protein-coupled receptors (GPCRs) due to the fact that part of the downstream signaling relies on an activation of heterotrimeric G proteins. The neutrophil GPCRs share significant sequence homologies but bind many structurally diverse ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 117 publications
8
66
0
Order By: Relevance
“…Our finding that the ability of FPR1 agonists to trigger neutrophil migration is linked to the ability to recruit -arrestin is in agreement with the emerging concept of biased FPR agonism and functional selectivity shown to be valid also for FPR2. [29][30][31]45,68,69 Our data are also in line with the documented role of -arrestin in regulating cell migration in studies performed with other cell types, including neutrophillike HL60 cells. [70][71][72][73] At the structural level, these data suggest that is not reduced by a G q inhibitor, and this is in line with earlier studies that have identified the part of a G i containing G protein downstream of FPR1, to be the link between the receptor an activation of the PLC-PIP 2 -IP 3 -Ca 2+ pathway.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our finding that the ability of FPR1 agonists to trigger neutrophil migration is linked to the ability to recruit -arrestin is in agreement with the emerging concept of biased FPR agonism and functional selectivity shown to be valid also for FPR2. [29][30][31]45,68,69 Our data are also in line with the documented role of -arrestin in regulating cell migration in studies performed with other cell types, including neutrophillike HL60 cells. [70][71][72][73] At the structural level, these data suggest that is not reduced by a G q inhibitor, and this is in line with earlier studies that have identified the part of a G i containing G protein downstream of FPR1, to be the link between the receptor an activation of the PLC-PIP 2 -IP 3 -Ca 2+ pathway.…”
Section: Discussionsupporting
confidence: 87%
“…Recent research suggests that the receptor crosstalk hierarchy is complex and not only desensitized receptors but also allosteric modulated GPCRs can communicate with other receptors. 45,49,50 A prominent example of such a crosstalk is that FPRs signaling can be positively regulated by free fatty acid receptor 2 (FFAR2) as illustrated by the fact that neutrophils with their FFARs allosterically modulated are primed when activated by low (normally nonactivating) concentrations of FPR agonists. 51,52 The fact that RE-04-001 response induced in neutrophils in the presence of an allosteric FFAR2 modulator, is inhibited not only to an FPR1 antagonist but also by an antagonist specific for FFAR2 (Fig.…”
Section: Re-04-001 Promotes Fpr1 To Crosstalk With Other Neutrophil Rmentioning
confidence: 99%
“…However, it has been established that there is no direct link between GPCR-mediated activation of the oxidase and the transient rise in [Ca 2+ ]i [5,18,32,39,40], which gains further support from the data presented in this study. Hence, even although it is difficult to directly correlate NADPH-oxidase activity and calcium signaling during receptor reactivation induced by Barbadin or latrunculin A, our data corroborate previous studies demonstrating that a rise in [Ca 2+ ]i is not a requirement for activation of the NADPH-oxidase.…”
Section: Discussionsupporting
confidence: 68%
“…Such an allosteric GPCR modulation is, according to the dogma for allosteric GPCR-modulation, solely affecting the signaling properties of agonists that specifically interact with the receptor that is allosterically modulated (6,7). This GPCR-modulation dogma has, however, been challenged and shown to be more complex than initially anticipated, when it was shown that allosteric modulators specific for Free Fatty Acid Receptor 2 (FFAR2) affect signaling mediated not only by orthosteric FFAR2 agonists but also by specific agonists for the ATP-receptor P2Y2R and for formyl peptide receptors (FPRs; (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%